Implementasi Kursus Calinda di Kabupaten Pidie - Huwaida, Huwaida; Ridha, Usfur (Universitas Islam Negeri Ar-Raniry, 2017)
This article is part of research which is funded by DIPA UIN Ar-Raniry 2016. This article tries to extract the long research report that studied the implementation of pre-marital training regulation circulated by a sub division in ministry of religious affairs in Indonesia. Through a qualitative approach Pidie district is purposively selected, this research tried to find the implementation process of pre-marital training and obstacle encountered during implementation of pre-marital training in Pidie district. To get a variety of views for this research, data were collected using interview with a KUA leader and five married residents. The research